Exploring Blended Peer-Assisted Learning in Undergraduate Medical Education - Wahid, Iqbal (International Journal of Pathology, 2022)
Background: Blended Peer-Assisted Learning (ePAL) platform consists basically on the integration of different existing e-Learning tools and platforms in a coordinated way in order to provide the implementation of PAL strategies. In this context, methodologies, techniques and innovating tools, supported by Information and Communication Technologies (ICTs) have been developed to promote better educational experiencesObjective: To explore the blended Peer assisted learning in undergraduate medical educationMaterial and Methods: A qualitative single case study in which 4 focus group discussions and two in depth interviews have been conducted from medical students of 3rd year MBBS. North West School of medicine is taken as one case, selected through purposive sampling technique. Each FGD was audio-recorded, transcribed verbatim, analyzed and themes were identified.Results: Total 22 students participated in 4 focus group discussions and 2 in-depth interviews. Six themes that emerged were” Learning Environment” indicates as a vital factor in effective teaching and learning “Concept Building and Comprehension” indicates understanding the subject matter of the course and clarifying basic and complex concepts “Developing Academic” indicating a PAL learning experience is a good learning experience to improve academics. “PAL in the regular teaching program “indicates that same year, equal status model of PAL should be part of regular teaching. “Operationalize aspect of PAL” indicating formal training sessions for peer tutors prior to proper PAL sessions improves its effectiveness in delivery of content. “Accomplishment of learning “indicating that peer learners plan and lead their own learning activities with a greater willingness to acquire knowledgeConclusion: The concept of providing and receiving feedback is deficient and its significance with respect to teaching and learning is lacking. Contextual academic workload and time constraints may impact the quality and timing of feedback provided. There is need of collaborations between university administration and faculty so that feedback can be utilized effectively in the learning process